Applying Artificial Neural Networks for analysis of geotechnical problems - Sulewska, Maria J. (Computer Assisted Methods in Engineering and Science, 2017)
The paper presents a discussion of some applications of Artificial Neural Networks (ANNs) in geoengineering using the analysis of the following six geotechnical problems, related mainly to prediction and classification purposes: 1) prediction of Overconsolidation Ratio (OCR), 2) determination of potential soil liquefaction, 3) prediction of foundation settlement, 4) evaluation of piles bearing capacity, 5) prediction of compaction parameters for cohesive soils, 6) compaction control of embankments built of cohesionless soils. The problems presented are based on the applications of the Multi-Layered Perceptron (MLP) neural networks.